Menumbuhkan Jiwa Kewirausahaan Bagi Siswa/Siswi SMA Pallawa Bengkulu - Edwarman, Edwarman; Sarfah, Betty; Novanda , Dwi Yenni (Jurnal Kewirausahaan dan Bisnis, 2021)
Entrepreneurship education in schools has become an important focus in developing the entrepreneurial potential of the younger generation. This study aims to analyze effective programs in fostering entrepreneurial spirit for students of Pallawa High School in Bengkulu City. The research method used is a survey with questionnaires distributed to students of SMA Pallawa. The results showed that entrepreneurship training programs, entrepreneurship practice lessons, and entrepreneurship-oriented extracurricular activities have a significant positive impact in increasing students' entrepreneurial interests and skills. The implication of this research is the need to increase entrepreneurship programs in schools as part of the effort to form a young generation that is creative, innovative, and ready to compete in the business world.